The Effectiveness of Combining Scripting and Talking Chips on the Students’ Speaking Achievement - Annisa Rahmasari; Ratna Nurlia (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2022)
This research is to find the effectiveness of combining Scriting and Talking Chips which helps students to be more active in speaking class. This research used quasi-experimental research with non-randomized pretest posttest design. The students of English Department of UNIPA Campus Blitar who took Basic Speaking 1 were the subjects of this research, in which Class A as the experimental group and class B as the control group. The instruments of this research were speaking test (pretest and posttest). One group was taught by combining scripting and talking chips method, in contrast, the control group was taught by using direct method. Then, both groups were given a posttest. The data was analyzed using ANCOVA and computed by SPSS version 20. The result of the analysis indicated that combining Scripting and Talking Chips strategy could make students’ speaking achievement better.